Contesting Commemoration : The 1876 Centennial, Independence Day, and the Reconstruction-Era South - Noe, Jack (Book collections on Project MUSE., 2021)
"Jack Noe's Contesting Commemoration examines identity and nationalism in the post-Civil War South through the lens of commemorative activity, namely the Independence Day celebrations and the Centennial of 1876. Held just eleven years after the end of a disastrous war that nearly tore the nation apart, the Centennial commemorating one hundred years of national existence presented an opportunity for whites, Blacks, northerners, and southerners to reflect on and engage with ideas about their identity as Americans. Although there is a considerable body of scholarly work on southern identities and attitudes during Reconstruction, comparatively few historians have examined southern reaction to or engagement with Independence Day or the Centennial to determine the condition of American nationalism in that era. Noe uses these commemorative activities to carry out a careful assessment of ex-Confederates' evolving relationship to the American nation, the return to power of the Democratic Party, and shifting regional and national identities. His work offers a new range of evidence and interpretation of white southern responses to these celebrations and explores the close connections between commemorative activities and the political concerns of the 1870s. In one example, Noe analyzes a heretofore overlooked episode of Centennial-related politicking in Texas that provides a compelling illustration of how contested, and how political, commemoration was in the Reconstruction Era. Throughout the study, Noe discusses Black engagement with commemoration and American identity, providing a useful counterpoint to his discussion of the reactions of southern whites. To illuminate the long-neglected history of commemoration in 1876, Noe explores an array of contemporary source material that reflects a broad sample of political and regional perspectives. The often colorful and engaging discourse surrounding these events provides a fascinating portrait of this fractured moment in the development of American identity and nationalism"--